2016
DOI: 10.1136/ejhpharm-2016-000984
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an integrated medicines management service on preventable medicines-related readmission to hospital: a descriptive study

Abstract: BackgroundMedication contributes to 5–20% of hospital admissions, of which half are considered preventable. An integrated medicines management service (IMMS) was developed at a large general hospital in London to identify and manage patients at risk of a preventable medicines-related readmission (PMRR) to reduce the risk of PMRR.ObjectiveTo investigate the effect of the pharmacy IMMS on the rate of PMRR within 30 days of the first discharge.Method744 patients were identified between October 2008 and October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Patients described experiencing medication discrepancies including wrong frequency, incorrect time, dosage or missed prescription regime following discharge from hospital because of poor communication and lack of clear and adequate information about their medications 68,70 . In some quantitative studies, interventions that focused on communication with patients, primary care physicians (PCPs) and community pharmacists after patients' discharge improved the discharge experience and enabled patients to manage their medications properly at home, leading to reduced medication-related hospitalisation rates 56,78 . and clearly written instructions of their current treatment plan and provision of discharge summaries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients described experiencing medication discrepancies including wrong frequency, incorrect time, dosage or missed prescription regime following discharge from hospital because of poor communication and lack of clear and adequate information about their medications 68,70 . In some quantitative studies, interventions that focused on communication with patients, primary care physicians (PCPs) and community pharmacists after patients' discharge improved the discharge experience and enabled patients to manage their medications properly at home, leading to reduced medication-related hospitalisation rates 56,78 . and clearly written instructions of their current treatment plan and provision of discharge summaries.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies addressed the theme of communication strategies to enable older patients' medication knowledge 53,54,56,60,63,67,71,72,74,76,80,82,85 . There were three subthemes for this theme: individualised discharge summaries, pharmacists' interventions and improvements in older patients' medication knowledge through medication education.…”
Section: Theme 4 Communication Strategies To Enable Older Patients' mentioning
confidence: 99%
“…This program of work is currently being evaluated but preliminary data suggests that a combination of support is desirable, including formal training, group workshops and one-to-one practice based visits [ 39 , 40 ]. The coaching approach was central to the development of an integrated medicines management service [ 41 ] and health coaching training has now been commissioned for healthcare professionals working in the Northwest London area [ 39 ].…”
Section: Using Health Coaching To Support Adherence Through Personmentioning
confidence: 99%
“…Some studies have even evidenced the causality associated, highlighting warfarin as a “definitely” responsible for GI bleeds . However, it has been shown that services like the integrated medicines management is effective in reducing the risk of hospital re‐admissions, a service where pharmacists play a key role …”
Section: Resultsmentioning
confidence: 99%
“…80 However, it has been shown that services like the integrated medicines management is effective in reducing the risk of hospital readmissions, a service where pharmacists play a key role. 81,82 Five to twenty percent of hospital admissions are caused by medication misuse and more than half of these are avoidable. Medication nonadherence is one of the areas for concern, as it is estimated that 11% to 22% of hospital admissions for exacerbations of chronic disease are a direct result of it.…”
Section: Secondary Care For Episodes Of Ill Healthmentioning
confidence: 99%